Hubungan Dukungan Keluarga dengan Kepatuhan Diet pada Lansia dalam Pengendalian Hipertensi di Puskesmas Kedungmundu - Risa Kisnawati; Moch. Aspihan; Iskim Luthfa (Pusat Riset dan Inovasi Nasional, 2025)
Background: The frequency of hypertension continues to increase in line with the low compliance of hypertension sufferers in carrying out their treatment, one of which is a hypertension diet. Family support plays a crucial role in increasing self-confidence, motivation, and life satisfaction of hypertension sufferers. Family involvement in health education programs helps patients with their needs met, understanding when to seek medical help, and support for treatment compliance, which can prevent recurrence and serious complications due to hypertension. In addition, compliance with a hypertension diet is very important to keep blood pressure stable. A good understanding of the benefits of diet and the role of family and health workers in providing support can increase diet compliance. Conversely, low understanding can reduce awareness of the importance of diet, potentially causing ongoing complications. Therefore, hypertension management strategies must involve family support and education about the right diet to achieve optimal health outcomes. This study was conducted to analyze the Relationship Between Family Support and Diet Compliance in the Elderly in Controlling Hypertension at the Kedungmundu Health Center. Methods: This study uses a quantitative method with a correlational approach. Data were collected through demographic questionnaires, family support, and hypertension diet compliance, with a study sample consisting of 90 people using random sampling techniques. Somers' D test was chosen as the statistical analysis method for this research data. Results: Based on the study, it was found that some respondents received quite good family support, with a total of 57 people (63.3%) and were quite compliant with dietary compliance as many as 57 people (63.3%). The results of the Somers' D test showed that the significance value of p = 0.000 <α (0.05), so H0 was rejected. Conclusion: Based on the data analysis, the conclusion obtained is that there is a relationship between family support and dietary compliance in the elderly in controlling hypertension at the Kedungmundu Health Center, Semarang City.